Contextualization and Assessing the Distribution Pattern of Bird Nest in Jahangirnagar University Campus - Khan, Md. Naimur Rahman; Lima, Mst. Riyana Evashe; Rashid, Md. Shahedur (The Jahangirnagar Review, 2025)
Being aware of ecological processes in fast-growing urban areas is important for protecting biodiversity. Birds are useful indicators of how healthy and balanced an environment is. This study looks at where bird nests are found in different parts of Jahangirnagar University and tries to understand their nesting preferences. The research uses field surveys, photos, GPS mapping, and tools like GIS and NDVI to find key nesting areas. It also explores how vegetation, habitat types, and human activity affect where birds build nests. The results show that birds prefer quiet areas with thick vegetation, and that nest numbers vary between land and water habitats. This study provides useful information for future research and emphasizes the need to protect different types of habitats to support bird diversity in city areas.